How fast can the European eel ( Anguilla anguilla ) larvae cross the Atlantic Ocean? - SYLVAIN BONHOMMEAU; BRUNO BLANKE; ANNE‐MARIE TRÉGUIER; NICOLAS GRIMA; ETIENNE RIVOT; YOUEN VERMARD; ERIC GREINER; OLIVIER LE PAPE (Fisheries Oceanography, 2009)
The migration duration of European eel ( Anguilla anguilla ) larvae (leptocephali) from the spawning areas in the Sargasso Sea to the European continental shelf remains highly controversial, with estimates varying from 6 months to more than 2 yr. We estimated the fastest migration period and the shortest distance travelled by eel larvae by simulating Lagrangian particles released in the Sargasso Sea and by simulating a range of larval behaviours (fixed‐depth drift, vertical diurnal migration and active‐depth selection to maximize current velocity). This enabled us to compute (i) a passive drift speed, and (ii) a hypothetic swimming speed needed for European eel larvae to cross the Atlantic in 6 months (i.e., the migration duration estimated from otolith daily growth increments). Our results show that the minimum travel time for an eel larva that is passively drifting was 10 months and 3 days. Active behaviours (vertical diurnal migration and rheotaxis) paradoxically increased the migration period. We found that for leptocephali to cross the Atlantic Ocean in 6 months, they would need to swim a minimum of 3.4 body lengths per second for 8200 km. No larvae have been observed with such swimming capabilities. These results provide evidence that leptocephali cannot cross the Atlantic in 6 months.